The structural and functional brain alternations in tobacco use disorder: a systematic review and meta-analysis - Ma, Longyao; Tao, Qiuying; Dang, Jinghan; Sun, Jieping; Niu, Xiaoyu; Zhang, Mengzhe; Kang, Yimeng; Wang, Weijian; Cheng, Jingliang; Zhang, Yong (Frontiers in Psychiatry, 2025)
BackgroundWhile numerous previous studies have indicated that nicotine intake results in gray matter and functional brain abnormalities in tobacco use disorder (TUD), the majority of results could not be replicated or even reversed. Consequently, it is important to utilize relevant coordinate data for a comprehensive meta-analysis to identify the shared patterns of structural, functional, and multimodal alternations in TUD.MethodThe present study conducted a systematic retrieval of studies published on PubMed, Web of Science, and Scopus from January 1, 2010, to December 12, 2023, to identify studies on voxel-based morphometry (VBM) and resting-state functional magnetic resonance imaging (rs-fMRI) for TUD. Then, two meta-analyses using the anisotropic seed-based d mapping method were used to detect brain comprehensive alterations in individuals with TUD. Furthermore, two meta-analyses were pooled for multimodal analysis to discover multimodal anomalies. Finally, subgroup analyses were performed to explore the sources of TUD heterogeneity from both methodological and age perspectives.ResultThis study encompassed a total of 25 VBM studies, including 1,249 individuals with TUD and 1,874 healthy controls (HCs), and 35 rs-fMRI studies, including 1,436 individuals with TUD and 1,550 HCs. For rs-fMRI analysis, individuals with TUD exhibited increased intrinsic function in the right cerebellum crus2, left superior frontal gyrus, left inferior parietal gyrus, and left supplementary motor area and decreased intrinsic function in the right gyrus rectus, right superior/middle frontal gyrus, and left inferior frontal gyrus. For VBM analysis, individuals with TUD showed decreased gray matter volume (GMV) in the left superior temporal gyrus, right superior frontal gyrus, right anterior cingulate/paracingulate gyrus, left superior frontal gyrus, and right anterior thalamic region and increased GMV in the right lingual gyrus.ConclusionThis meta-analysis illustrates structural and functional abnormalities of the default mode network, executive control network, and salience network in individuals with TUD. Multimodal analysis of the right lingual gyrus provided additional information, offering the potential for identifying more therapeutic targets for interventions against TUD.